AN ECONOMIC ANALYSIS OF THE MOST IMPORTANT FACTORS AFFECTING AGRICULTURAL GROWTH IN IRAQ USING ARDL MODEL - & AlBadri, Alattabi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This research was aimed to study some factors influencing agricultural growth in Iraq. Using time series data for the period 1990 – 2017, of agricultural growth (a dependent variable) and agricultural exports, agricultural imports, agricultural fixed capital and the agricultural labor force (as independent variables). For these purposes, were statistical and econometrics methods employed to determine the most important aspects of this problem in agricultural sector. Co-integration analysis was used which developed by Johansen, also Augmented Dicky – Fuller of unit root test to determine non stationary data for choosing the best analysis method. In light of results, Auto-Regressive Distributed Lag model (ARDL) was used in assessment and analysis. The results showed presence of co-integration in both agricultural imports and agricultural labor force with elasticity coefficients (-0.3 and-0.6), respectively and significant at 1% and 5% levels respectively, and lack of co-integration of both the agr.exports and agricultural fixed capital with elasticity coefficients (0.2 and 0.03) respectively which they are not significant.